Analysis of the Application of Business Ethics Theory in the Case of Bribery Acceptance By the Audit Board of Indonesia (BPK RI) in 2023 - Wahyuni Susilowati; Sri Trisnaningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This case research aims to explore the theory of business ethics and analyze its implementation by examining a case of business ethics violations involving the Supreme Audit Agency (BPK RI), which accepted bribes during audit activities at the Public Works and Spatial Planning Service (PUTR) in South Sulawesi. Based on the case analysis, it was found that three auditors committed violations, including manipulating the budget items under review, inflating the budget (markups), discrepancies between the work outcomes and the contracts, and accepting bribes totaling IDR 2.8 billion. The actions of the auditors align with egoism theory, but they also violate several business ethics theories, including utilitarianism, Kantian ethics and deontological ethics, and virtue ethics. As a consequence of these actions, the BPK auditors faced sanctions, including imprisonment and fines.